Bone mineral density and bone metabolism in patients with Duchenne muscular dystrophy - Barzegar, Mohammad; NIKNAM, Elnaz; HABIBI, Parinaz; SHIVA, Shadi; TAHMASEBI, Sanaz (Iranian Journal of Child Neurology, 2018)
ABSTRACT Objective: Poor bone health with related morbidity is a major problem with Duchene Muscular Dystrophy (DMD). Decreased mobility and long-term corticosteroid therapy are involved in poor bone health in DMD. This study investigates bone mineral density and bone metabolism in 30 steroid treated DMD patients and also comparison of mentioned factors between ambulated and non-ambulated patients. Materials & Methods: In this cross-sectional study 30 boys (21 patients ambulate and 9 non-ambulate) with documented DMD, according to genetic analysis, were enrolled. Demographic characteristics, neurologic exam findings, muscle function score, corticosteroid dose and duration and food frequency questionnaire were recorded. Bone mineral density was measured with dual- energy X-ray absorptiometry (DEXA) on lumbar spine and left proximal femur. Serum 25-hydroxyvitamin D, calcium, phosphorus and parathyroid hormone (PTH) levels were measured. Results: Osteoporosis was found in 86.7% patients. Mean bone density in the lumbar spine was -1.5±0.24 and -1.4±0.27 in ambulates and non-ambulates respectively (P=0.7). Mean bone density at proximal femur was -3.4±0.2 in ambulates and -3.4±0.3 in non-ambulates (p =0.48). Intra-groups statistical analysis showed significant difference between bone mineral density at lumbar spine and proximal femur in both mentioned groups (P<0.05). Vitamin D deficiency was detected in 13 patients (43.3%) and its serum level was significantly lower in non-ambulates compared with ambulates. Conclusion: High prevalence of vitamin D deficiency and osteoporosis was found in DMD patients although osteoporosis severity was not affected by muscle function and ambulation. So it seems that vitamin D supplementation can improve vitamin D status and osteoporosis in these patients, especially in non-ambulates.